Association of sex with clinical outcomes in COVID-19 patients: A retrospective analysis of 1190 cases. (November 2020) - Liu, Jiao; Zhang, Lidi; Chen, Yizhu; Wu, Zhixiong; Dong, Xuan; Teboul, Jean-Louis; Zhang, Sheng; Ye, Xiaofei; Liu, Yongan; Wang, Tao; Du, Hangxiang; Li, Wenzhe; et al.
Abstract: Background: The outbreak of COVID-19 caused by SARS-CoV-2 has been a pandemic. The objective of our study was to explore the association between sex and clinical outcomes in patients with COVID-19. Methods: Detailed clinical data including clinical characteristics, laboratory tests, imaging features and treatments of 1190 cases of adult patients with confirmed COVID-19 were retrospectively analyzed. Associations between sex and clinical outcomes were identified by multivariable Cox regression analysis. Results: There were 635 (53.4%) male and 555 (46.6%) female patients in this study. Higher rates of acute kidney injury (5.5% vs. 2.9%, p = 0.026), acute cardiac injury (9.1% vs. 4.3%, p = 0.001), and disseminated intravascular coagulation (2.5% vs. 0.7%, P = 0.024) were observed in males. Compared with female patients, male patients with COVID-19 had a higher inhospital mortality rate (15.7% vs . 10.3%, p = 0.005). However, Cox regression analysis showed that sex did not influence inhospital mortality of COVID-19 patients. Conclusions: Male sex was associated with a worse prognosis of COVID-19, but it seems not to be an independent prognostic factor.